Carbon-based negative electrode material and preparation method thereof, negative electrode and sodium ion battery

Through the roasting method of nano-scale blenite and starch, the foaming and fusion of starch-based carbon anode materials are inhibited, and the morphology and conductivity are improved, and the problems of poor stability and unsatisfactory electrochemical performance of starch-based carbon anode materials are solved, thereby achieving higher sodium storage capacity and battery performance.

CN119812320AActive Publication Date: 2025-04-11JIANGSU PYLON BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510283707.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

Starch-based carbon anode material is prone to foaming, melting and volume expansion during the preparation process, resulting in irregular morphology, affecting performance, poor stability and unsatisfactory electrochemical performance.

Method used

Nano-scale blenmus and starch are used for calcination, and alumina is generated by pyrolyzing blenmusite and starch is carbide by carbide at high temperature to form a mixture of aluminum nitrogen and alumina coated on the surface of the starch, inhibiting foaming and fusion, and improving morphology and electrical conductivity.

Benefits of technology

Effectively inhibit the foaming and fusion of starch particles, improve the particle morphology, generate more disordered sodium storage layers, improve capacity and conductivity, increase the high and low temperature stability of the SEI film, reduce side reactions, and improve the cycle life and rate performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a carbon-based negative electrode material and a preparation method thereof, a negative electrode and a sodium ion battery. The preparation method of the carbon-based negative electrode material comprises the steps that mixed powder is provided, and the mixed powder comprises starch and nanoscale boehmite powder which are mixed with each other; in the nitrogen atmosphere, the mixed powder is placed at the temperature of 400-500 DEG C for pyrolysis of bombardment mother stone, the bombardment mother stone is fully decomposed to generate aluminum oxide and water, and the carbon material is etched; and carbonizing the starch at a high temperature of 1100-1500 DEG C, and generating a mixture of aluminum nitrogen and aluminum oxide to coat the carbon material. The carbon-based negative electrode material prepared by the preparation method provided by the invention has relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a carbon-based negative electrode material and a preparation method thereof, a negative electrode and a sodium ion battery. Background Art

[0002] In order to improve the sodium storage capacity and sodium electrical performance of sodium batteries, starch can be considered as a carbon source material to replace the raw materials and biomass hard carbons such as shells, bamboo, and reeds with poor morphology consistency. However, during the preparation process, starch carbon sources will foam, melt, and expand dramatically in volume, which brings difficulties to material preparation. In addition, the morphology of the material particles after foaming and melting is irregular, which will also affect the final performance. In response to this problem, the poor stability and unsatisfactory electrochemical performance of starch-based carbon negative electrode materials have not yet been effectively solved.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The present invention aims to improve at least one of the problems mentioned in the background art.

[0005] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a carbon-based negative electrode material, comprising: Providing a mixed powder, the mixed powder comprising starch and nano-scale boehmite powder mixed with each other; The mixed powder is placed at 400-500° C. to pyrolyze boehmite, so that the boehmite is fully decomposed to generate alumina; and then the starch is carbonized at 1100-1500° C. at high temperature.

[0006] In an optional embodiment, the time for pyrolyzing boehmite is 0.5 to 2 hours.

[0007] In an optional embodiment, the high temperature carbonization time is 2 to 5 hours.

[0008] In an optional embodiment, the high temperature carbonization process is performed in a nitrogen atmosphere.

[0009] In an optional embodiment, at least one of the following features (1) and (2) is included: (1) The D50 and D90 of the starch are 4-9 μm and 10-20 μm, respectively; (2) The mass ratio of starch to the nano-sized boehmite is 100:5-20.

[0010] In an optional embodiment, the starch is selected from at least one of corn starch, sweet potato starch, potato starch, cassava starch, sweet potato starch, water chestnut starch and lotus root starch.

[0011] In a second aspect, the present invention provides a carbon-based negative electrode material prepared by the preparation method described in any one of the aforementioned embodiments.

[0012] In a third aspect, the present invention provides a negative electrode, wherein the composition layer of the active coating thereof includes the carbon-based negative electrode material as described in the above embodiment.

[0013] In a fourth aspect, the present invention provides a sodium ion battery comprising the negative electrode described in the aforementioned embodiment.

[0014] The present invention has the following beneficial effects: The preparation method provided by the present invention adopts nano-scale boehmite and starch to mix and bake, which can realize local physical barrier and constraint on starch, effectively inhibit the foaming and melting of starch particles during heating, improve particle morphology, and inhibit the orderly growth of microcrystalline structure to generate more disordered sodium storage layers; not only that, after the boehmite is pyrolyzed, the generated water vapor and starch react to etch the material, generate pore size, and increase capacity. The generated alumina will generate aluminum nitrogen and aluminum oxide mixture coated on the starch surface after high-temperature calcination, and improve the conductive performance of the material. In addition, aluminum nitrogen and aluminum oxide particles participate in the formation of SEI film, increase the high and low temperature stability of SEI film, reduce side reactions, and improve the cycle life and rate performance of battery cells. Boehmite and starch are used as raw materials, with low cost, one-time firing process, and simple production process. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0016] An embodiment of the present invention provides a method for preparing a carbon-based negative electrode material, comprising: Providing a mixed powder, the mixed powder comprising starch and nano-scale boehmite powder mixed with each other; The mixed powder is placed at 400-500° C. to pyrolyze boehmite, so that the boehmite is fully decomposed to generate alumina; and then the starch is carbonized at 1100-1500° C. at high temperature.

[0017] The preparation method uses nano-scale boehmite and starch to mix and roast, which can achieve local physical barrier and constraint on starch, effectively inhibit the foaming and melting of starch particles during heating, improve particle morphology, and inhibit the orderly growth of microcrystalline structure to generate more disordered sodium storage layers; not only that, after the boehmite is pyrolyzed, the generated water vapor and starch react to etch the material, generate pores, and increase capacity. The generated alumina will be mixed and coated on the starch surface after high-temperature calcination, improving the conductive properties of the material. In addition, alumina particles participate in the formation of SEI film, increase the high and low temperature stability of SEI film, reduce side reactions, and improve the cycle life and rate performance of the battery cell. Boehmite and starch are low-cost raw materials, the process is fired once, and the production process is simple.

[0018] Specifically, the preparation method is: S1. Preparation of mixed powder (1) The starch is ground and classified to obtain powders with particle sizes D50 and D90 of approximately 4~9μm and 10~20μm, respectively.

[0019] Optionally, the starch is selected from at least one of corn starch, sweet potato starch, potato starch, cassava starch, sweet potato starch, water chestnut starch and lotus root starch.

[0020] (2) Dry-mixing starch and nano-sized boron nitrate powder to uniformly obtain a mixed powder.

[0021] Optionally, the mass ratio of starch to nano-sized boehmite is 100:5-20 (eg, 100:5, 100:10 or 100:20).

[0022] S2. Heat treatment The mixed powder is placed at 400-500°C (e.g., 400°C, 450°C, or 500°C) to pyrolyze boehmite, so that the boehmite is fully decomposed to generate alumina; and then the starch is carbonized at 1100-1500°C (e.g., 1100°C, 1200°C, 1300°C, or 1500°C).

[0023] Preferably, the treatment time at 400-500° C. (eg, 400° C., 450° C., or 500° C.) is 0.5-2 h (eg, 0.5 h, 1 h, or 2 h).

[0024] Preferably, the treatment time at 1100-1500° C. is 2-5 h (eg, 2 h, 3 h or 5 h).

[0025] Preferably, the high-temperature carbonization process is carried out in a nitrogen-containing atmosphere. At 1100-1500°C (e.g., 1100°C, 1200°C, 1300°C, or 1500°C), starch can be carbonized, and the aluminum oxide is partially reduced by carbon and reacts with the nitrogen-containing atmosphere to generate a mixture of aluminum nitrogen and aluminum oxide. The generated aluminum nitrogen can also improve the conductivity of the material and participate in the formation of the SEI film, increasing the high and low temperature stability of the SEI film. In addition, the doping of N elements into the negative electrode material can further increase the electron migration rate.

[0026] An embodiment of the present invention provides a carbon-based negative electrode material, which is prepared by the preparation method provided by the present invention.

[0027] An embodiment of the present invention provides a negative electrode, wherein the composition layers of the active coating layer include the carbon-based negative electrode material provided by the embodiment of the present invention.

[0028] Specifically, the preparation method of the negative electrode is, for example: The carbon-based material provided in an embodiment of the present invention is prepared into a slurry according to the ratio of carbon material: carbon black: CMC: SBR = 94: 1.5: 1.7: 2.8, and the slurry is coated on an aluminum foil to obtain a negative electrode sheet.

[0029] A sodium ion battery provided in an embodiment of the present invention comprises the negative electrode provided in an embodiment of the present invention.

[0030] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0031] Example 1 Potato starch with a D50 and a D90 of about 5 μm and 15 μm respectively and boehmite powder with a particle size range of 20-100 nm are uniformly mixed in a mass ratio of 100:10 to obtain a mixed powder; Nitrogen was introduced into the sintering furnace, the mixed powder was placed in the sintering furnace, the temperature was raised to 450°C and sintered for 1 hour, then the temperature of the sintering furnace was raised to 1200°C, and high-temperature carbonization was performed for 3 hours to obtain a carbon-based material.

[0032] Example 2 Cassava starch with a D50 and a D90 of about 4 μm and 10 μm respectively and sphaerocarp powder with a particle size range of 20 to 100 nm are uniformly mixed in a mass ratio of 100:5 to obtain a mixed powder; Nitrogen was introduced into the sintering furnace, the mixed powder was placed in the sintering furnace, the temperature was raised to 400°C and sintered for 2 hours, and then the temperature of the sintering furnace was raised to 1500°C and high-temperature carbonization was performed for 2 hours to obtain a carbon-based material.

[0033] Example 3 Corn starch with a D50 and a D90 of about 9 μm and 15 μm respectively and boehmite powder with a particle size range of 20-100 nm are uniformly mixed in a mass ratio of 100:20 to obtain a mixed powder; Nitrogen was introduced into the sintering furnace, the mixed powder was placed in the sintering furnace, the temperature was raised to 500°C and sintered for 0.5 h, and then the temperature of the sintering furnace was raised to 1100°C and high-temperature carbonization was performed for 0.5 h to obtain a carbon-based material.

[0034] Example 4 This embodiment is basically the same as the embodiment 1, except that argon gas is introduced into the sintering furnace instead of nitrogen gas.

[0035] Comparative Example 1 This comparative example is basically the same as Example 2, except that after the mixed powder is placed in the sintering furnace, the temperature is directly raised to 1600° C. (the second temperature) and sintered for 2 hours.

[0036] Comparative Example 2 This comparative example is basically the same as Example 3, except that boehmite is replaced by nano-alumina, and the mass ratio of starch to alumina is 100:4.25.

[0037] Comparative Example 3 This comparative example is substantially the same as Example 3, except that no boehmite is added.

[0038] Comparative Example 4 This comparative example is basically the same as Example 1, except that the starch is replaced by an equal amount of bamboo biomass powder.

[0039] Experimental Example 1 The negative electrode materials prepared in each embodiment and comparative example were prepared into negative electrode sheets. The specific method was as follows: a slurry was prepared according to the ratio of carbon material: carbon black: CMC: SBR = 94: 1.5: 1.7: 2.8 and coated on aluminum foil to obtain a negative electrode sheet.

[0040] The negative electrode sheets are assembled into a battery. The specific method is as follows: NFPP: carbon black: CNT: PVDF are mixed in a ratio of 96:1.2:1.1:1.7 to prepare a slurry, which is then coated on aluminum foil to make a positive electrode sheet; the positive electrode sheet, the prepared negative electrode sheet and the PP separator are assembled into a sodium ion battery, and the electrolyte is 1 mol / LNaPF6, 40%PC+60%EMC.

[0041] The electrochemical performance of the battery was tested and the test results were recorded in Table 1.

[0042] Table 1 Performance statistics of batteries prepared in various embodiments and comparative examples

[0043] It can be seen from Table 1 that the negative electrode materials prepared in various embodiments of the present invention have good electrochemical performance after being made into negative electrodes and assembled into batteries.

[0044] Comparing Example 4 with Example 1, the first effect of Example 4 is poor, which indicates that when nitrogen-containing gas is introduced and nitrogen is doped in the obtained carbon-based negative electrode material, the surface of the material can be further modified and irreversible reactions can be reduced.

[0045] Comparing Comparative Example 1 with Example 2, the rate performance of Comparative Example 1 is significantly worse than that of Example 1, indicating that if the boehmite is not pyrolyzed at the first temperature and high-temperature carbonization is directly performed, the battery capacity will be reduced due to insufficient reaction; Comparing Comparative Example 2 with Example 3, the rate performance of Comparative Example 2 is poor, indicating that if alumina is used to replace boehmite, since alumina will not decompose and will not etch starch during the sintering process, the internal pore size of the obtained negative electrode material will be small and the rate performance will be poor. Comparing Comparative Example 3 with Example 3, the cycle of Comparative Example 3 is poor, indicating that if boehmite is not added during the preparation of the carbon-based material, there is no inhibitory effect on the foaming and melting of starch, and the cycle life of the obtained carbon-based material is poor; Comparing Comparative Example 4 with Example 1, the cycle of Comparative Example 4 is poor, indicating that compared with biomass powder as a carbon source, starch can produce carbon-based materials with better consistency and more advantageous cycle life.

[0046] In summary, the preparation method provided by the present invention has the following characteristics: 1. In the present application, starch is doped and sintered, which effectively inhibits the foaming and melting of starch particles during the heating process, improves the particle morphology, and inhibits the orderly growth of the microcrystalline structure to generate more disordered sodium storage layers.

[0047] 2. The finished product fired in this application contains aluminum nitrogen and aluminum oxide particles, which participate in the formation of the SEI film, increase the high and low temperature stability of the SEI film, reduce side reactions, improve the cycle life and rate performance of the battery cell, and improve the conductivity of the material.

[0048] 3. Water vapor etching is used in this application to increase the capacity of the material.

[0049] 4. The present application adopts low-cost starch raw material and boehmite, which is mixed and fired once, which reduces the processing steps and is simple and low in cost.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-based negative electrode material, characterized in that: include: Providing a mixed powder, the mixed powder comprising starch and nano-scale boehmite powder mixed with each other; placing the mixed powder at 400-500° C. to pyrolyze boehmite, so that the boehmite is fully decomposed to generate alumina; Then, the starch is carbonized at 1100-1500°C.

2. The preparation method according to claim 1, characterized in that: The time for pyrolysis of pyrolysis stone is 0.5~2h.

3. The preparation method according to claim 1, characterized in that: The high temperature carbonization time is 2~5h.

4. The preparation method according to claim 1, characterized in that: The high temperature carbonization process is carried out in a nitrogen atmosphere.

5. The preparation method according to claim 1, characterized in that: The invention comprises at least one of the following features (1) and (2): (1) The D50 and D90 of the starch are 4-9 μm and 10-20 μm, respectively; (2) The mass ratio of starch to the nano-sized boehmite is 100:5-20.

6. The preparation method according to claim 1, characterized in that: The starch is selected from at least one of corn starch, sweet potato starch, potato starch, cassava starch, sweet potato starch, water chestnut starch and lotus root starch.

7. A carbon-based negative electrode material, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A negative electrode, characterized in that The composition layers of the active coating include the carbon-based negative electrode material as described in claim 7.

9. A sodium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 8.

Citation Information

Patent Citations

  • Method for preparing aluminum titanate-mullite composite porous ceramic from fly ash

    CN108178658A

  • Starch-based hard carbon negative electrode material and preparation method and application thereof

    CN118439588A

  • Composite materials comprising carbon nanotubes and metal carbonates

    CN1953935A

  • Lamp for vehicle

    KR1020250132192A